X-Chromosome Association Study in Latin American Cohorts Identifies New Loci in Parkinson S Disease - Chana-Cuevas, P (John Wiley and Sons Inc, 2023)
Background: Sex differences in Parkinson s disease (PD) risk are well-known. However, the role of sex chromosomes in the development and progression of PD is still unclear. Objective: The objective of this study was to perform the first X-chromosome–wide association study for PD risk in a Latin American cohort. Methods: We used data from three admixed cohorts: (1) Latin American Research consortium on the Genetics of Parkinson s Disease (n = 1504) as discover cohort, and (2) Latino cohort from International Parkinson Disease Genomics Consortium (n = 155) and (3) Bambui Aging cohort (n = 1442) as replication cohorts. We also developed an X-chromosome framework specifically designed for admixed populations. Results: We identified eight linkage disequilibrium regions associated with PD. We replicated one of these regions (top variant rs525496; discovery odds ratio [95% confidence interval]: 0.60 [0.478–0.77], P = 3.13 × 10−5 replication odds ratio: 0.60 [0.37–0.98], P = 0.04). rs5525496 is associated with multiple expression quantitative trait loci in brain and non-brain tissues, including RAB9B, H2BFM, TSMB15B, and GLRA4, but colocalization analysis suggests that rs5525496 may not mediate risk by expression of these genes. We also replicated a previous X-chromosome–wide association study finding (rs28602900), showing that this variant is associated with PD in non-European populations. Conclusions: Our results reinforce the importance of including X-chromosome and diverse populations in genetic studies. © 2023 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. © 2023 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.